Colloidal carbon dots based highly stable luminescent solar concentrators. (February 2018) - Zhou, Yufeng; Benetti, Daniele; Tong, Xin; Jin, Lei; Wang, Zhiming M.; Ma, Dongling; Zhao, Haiguang; Rosei, Federico
Abstract: Luminescent solar concentrators (LSCs) can serve as large-area sunlight collectors for photovoltaic (PV) cells, reducing the cost of PV generated power. Typical LSCs consist of optical waveguides doped with highly emissive fluorophores e.g. quantum dots (QDs) or dyes/polymers which are required to exhibit high optical efficiency and long-term stability. Compared to conventional fluorophores, carbon dots (C-dots) have superior advantages of non-toxicity, environmental friendliness, low-cost and simple preparation using abundant carbon based feedstock. Here, we demonstrate large-area LSCs (up to 100 cm 2 ) using colloidal C-dots. Two types of LSCs were fabricated by either incorporating oil-soluble oleylamine-treated C-dots into photo-polymerized poly(lauryl methacrylate) (PLMA) or spin-coating the water-soluble C-dots/polyvinylpyrrolidone (PVP) mixture on the glass substrate. LSCs based on C-dots/PLMA exhibit a quantum efficiency of 4% (geometric (G) factor of 38) and an optical efficiency of 1.1% (100 cm 2, G factor of 12.5) of tandem thin-film LSCs based on C-dots/PVP was achieved under one sun illumination. This performance is comparable to those of LSCs based on inorganic QDs with similar G factor. The LSCs based on C-dots are highly air-stable without any noticeable variation in photoluminescence under ultraviolet illumination (1.3 W/cm 2 ) for over 12 h. Graphical abstract: Highlights: The modified C-dots with broad absorption exhibits a quantum yield of ~ 30%. LSCs based on C-dots/PLMA exhibit a quantum efficiency of 4% (G of 38). Tandem LSCs based on C-dots exhibits an optical efficiency (100 cm 2 ) of 1.1%. The LSC is highly air-stable under UV light illumination for over twelve hours.